2017
DOI: 10.1007/s13762-017-1559-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-woven polypropylene fabric modified with carbon nanotubes and decorated with nanoakaganeite for arsenite removal

Abstract: Due to its harmful impact on human health, presence of heavy metals, metalloids and other toxic pollutants in drinking or irrigation water is a major concern. Recent studies have proven that nanosized adsorbents are significantly more effective than their microsized counterparts. Particular attention has been given to nanocomposites with nanoadsorbents embedded in matrixes that could provide stability to the material and contribute to eliminating problems that may appear when using conventional granular system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The experimental design matrix provides insights into the validities of dosage and pH on the removal percentages and adsorption capacities. The results demonstrated variations in performance based on the specific combination of variables, emphasizing the importance of optimizing these parameters for achieving high removal efficiency in the studied system 47 . Table 2 and Fig.…”
Section: Experimental Designmentioning
confidence: 92%
“…The experimental design matrix provides insights into the validities of dosage and pH on the removal percentages and adsorption capacities. The results demonstrated variations in performance based on the specific combination of variables, emphasizing the importance of optimizing these parameters for achieving high removal efficiency in the studied system 47 . Table 2 and Fig.…”
Section: Experimental Designmentioning
confidence: 92%
“…In this paper, the studies on the optimization of TC removal and multiwall carbon nanotube (MWCNTs) adsorption process by RSM-BBD were summarized, which were recorded in Tables S2 and S3. Table S2 [54][55][56][57] and Table S3 [ [58][59][60][61][62][63][64][65][66] showed that BBD could improve adsorption efficiency and save resources in the fields of MWCNTs adsorbent and TC removal, respectively [54,58]. At present, RSM-BBD optimization of MMWCNTs adsorption TC needs further practice.…”
Section: Introductionmentioning
confidence: 99%